Special interest tourism at Malaysian low tourism arrivals' states - Saad, Mazni (Perpustakaan Negara Malaysia, 2022)
The aim of this report is to recommend the development of special interest tourism for inbound tourism at low tourism arrivals (and receipts) states in Malaysia such as Perlis, Negeri Sembilan, Kelantan, and Kedah. The motivations and exhibited behavior of the tourists who traveled abroad to their favorite countries are analyzed carefully. The recommendations are based on both primary and secondary data with a careful judgment for a similar interest of tourists and speciality that is available in the low tourism arrivals (and receipts) states. Similar preferences and traveling motivations were tapped from Chinese tourists who came to Malaysia and Malaysian tourists who traveled to Japan, Saudi Arabia, and Taiwan. It is hoped that the idea would benefit the stakeholders especially in the respective low tourism arrival states to enhance the popularity of tourism destinations for a better income based on tourism products and services.